Strategi Perubahan Inovatif dalam Kepemimpinan Visioner Kepala Sekolah Muhammadiyah - Naomi Fahma; Anton Adi Suryo Kusuma; Harun Joko Prayitno; Bambang Soemardjoko; Sabar Narimo (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Leadership plays a strategic role in an organization and can significantly influence its performance. The role of a school principal's leadership can have both positive and negative impacts on the school. A positive influence from the principal's leadership can bring about changes, especially in Muhammadiyah schools. School transformation can be achieved when the principal, as a leader, has the competence to formulate innovative visions, missions, goals, and strategies for the school. This type of leadership with such competence can be referred to as visionary leadership. This study selects MI Taskombang in Klaten, Indonesia, as the research site. It employs a qualitative approach, specifically a case study design. The case study design is chosen because MI Taskombang has undergone significant changes in recent years and has become a benchmark and favored school. The objectives of this research are as follows: (1) to describe the role of visionary leadership by the principal, (2) to explore the effective strategies employed by the principal in implementing school changes, (3) to examine the innovations implemented by the principal in bringing about effective school changes, (4) to understand the process of change in the school, (5) to identify the supporting factors for the principal in implementing changes, and (6) to identify the hindering factors faced by the principal. Keywords: Innovative Change, Principal, Visionary Leadership